The epidemiology of meningococcal disease and the impact of vaccines. - Khatami, A; Pollard, A (2010)
Neisseria meningitidis causes endemic meningococcal disease worldwide. Serogroups B and C are responsible for the majority of cases of meningococcal disease in Europe, serogroups B, C and Y cause most disease in the Americas, and serogroups A, C and W135 predominate in Asia and Africa. Polysaccharide vaccines against meningococcal serogroups A, C, Y and W135 have been available for several decades, but have been little used due to poor immunogenicity in young children and minimal effects on nasopharyngeal carriage. Conversely, the introduction of the conjugate serogroup C meningococcal vaccine has dramatically changed the epidemiology of the disease in industrialized nations, showing potential for broader control with A, C, Y and W135 conjugates, and leaving serogroup B as the predominant cause of disease. Development of vaccines for prevention of serogroup B disease in industrialized nations and serogroup A conjugate vaccines for Africa could lead to global control of meningococcal disease.